Rare bird documentation form for Lesser Black-backed Gull at Ottumwa, 1997 - Dinsmore, Stephen J.et al (1997)
Rare bird documentation form for a Lesser Black-backed Gull at Ottumwa in Wapello County, IA on January 6, 1997. Epson - sheet feed